The place of poetry : two centuries of an art in crisis - Clausen, Christopher, 1942- (University Press of Kentucky, 1981)
Since the end of the eighteenth century, Christopher Clausen asserts, poetry has steadily declined in cultural status in the English-speaking world, yielding its former place as a bearer of truth to the advancing sciences. As the position of poetry was more and more threatened, its defenders made ever higher claims for its importance, even maintaining for a time that it would take the place of religion. But, though the Romantics brought about a sustained revival of serious poetry for a broad audience, the audience began to dwindle toward the end of the nineteenth century, and the decline accel.